Intestinal Coccidia - MJ Ggaravi (Tehran University of Medical Sciences, 2007)
Intestinal Coccidia are a subclass of Apicomplexa phylum. Eucoccidida are facultative heteroxenous, but some of them are monoxenous. They have sexual and asexual life cycle. Some coccidia are human pathogens, for example: Cryptosporidium: Cryptosporidiums has many species that are mammalian intestinal parasites.C. Parvum specie is a human pathogenic protozoa. Cryptosporidum has circle or ellipse shapes and nearly 4-6 mm. It is transmitted in warm seasons. Oocyst is obtained insexual life cycle that has 20% thin layer and 80% thick layer. Oocyst with thick layer is able to live a long time in nature. They are the third or forth of gastroentritis disease that have digestive disorder like anorexia, nausea, persistent diarrhoea, malabsorption and leanness. The disease forms choronic and acute stages and it is able to kill the immunodeficiency cases. Sometimes it has HIV symptoms similar to pneumonia and respiratory track infection. Laboratory diagnosis is based on Oocyst finding in stool exam and that shitter floatation and Cr (KOH)2 are the best methods. Modified zyh-lnelson and fleocroum are the best staining methods too. This parasite is transmitted by zoonotic and Antroponotic origin. Molecular studies have shown two Genotypes (I&II). Genotype I is aquatic and II is zoonotic. The prevalence rate is 3% in infants and 10% in calves. Cyclospora: This parasite is novel and is bigger than cryptosporidium.It isn't known a clear life cycle but is transmitted by water, vegetables and fruits as raspberries. and mulberries. Human is a specific host. When a parasite is in the intestine it causes inflammatory reaction in Entrocyte.The patient shows watery diarrhoea with nausea, vomitting, pain, Stomach cramp, anorexia, malabsorption and cachexia. The disease period is 3 monthes in immunodeficiency cases but it is selflimited in normal cases. Autofluorescence characteristic is differential diagnosis, prevalence rate of disease is unknown. Isospora: This intestinal parasite is in most parts of the world. Sometimes it is noun traveller diarrhea Syndrom. The egg shapes of Oocyst are disporic tetrazoic. It is transmitted by vegetables and fruits. Trophozoite pass through schizogony step and repeats it several times. In the end of the cycle gametogony is done and the sexual forms will be repelled the human intestine. Symptoms are persistent diarrhoea, epigastric pain, headache, fever, vomitting and leanness, especially when physiologic disorder condition is seen in patient or they are in traveling. Misdiagnosis is a problem in laboratories but floatation method with zinc sulfate or sugar syrup is recommended. Sarcocystis: Sporocyst of S.hominis and S. suihominis is in the human feces, and the cyst form is in pig and cow muscles. It founds in tha tongue, pharynx and oesophagus muscles of habitant buffalo in Iran. Because of the large size of the cyst (1cm), it is seen with naked eyes and the risk of human infection is rare. If human eats raw or uncooked cow and pig meat, he will be infected with it. Sexual cycle is in the human body and sporocyst is repelled by the intestine. The disease may or may not have any symptoms. The symptoms are diarrhoea, stomach cramp, jejenuom and ileum necrosis. Diagnosis is based on concentrated floatation. The prevalence rate is too much in domestic animals.